STRUCTURAL, MORPHOLOGICAL AND OPTICAL PROPERTIES OF RE-DOPED AZO THIN FILMS (RE=Nd, Gd, Er) GROWN BY RF MAGNETRON SPUTTERING - TOMA, Maria; MARCONI, Daniel; LUNG, Claudiu; PONTA, Oana; POP, Aurel (Studia Universitatis Babeș-Bolyai Chemia, 2015)
In this paper, we describe the influence of substrate-target distance of AlZnO films doped with rare earth (RE= Nd, Gd, Er) ions, on structural, morphological and optical properties. The transparent conductive RE doped AZO thin films were fabricated by radio frequency (RF) magnetron sputtering using a power of 100 W and the deposition pressure of 2.1 × 10−2 mbar. The deposition was performed on glass substrates heated at 1500C and with a time deposition of 90 minutes. Therefore, we obtained AZO thin films doped with RE ions. The influence of substrate-target distance for each rare earth ions on the structure of thin films was analyzed by X-ray diffraction (XRD). Scanning electron microscopy (SEM) shows the uniformity of the surface which consists of well-defined spherical crystallites. The decreasing of target-substrate distance leads to an increase in grain size. However, there is a slight change in the size and topography of films by doping with different 4f elements. The energy dispersive X-ray spectroscopic analysis (EDX) results show presence of an oxygen deficiency (oxygen stoichiometry lower than 50 wt.%). The optical transmittance through the films was measured in the wavelength range 375–1000 nm. The refractive index, transparency and thickness of obtained films were determined.